Parallel Algorithmic Optimization and Achievement for LDPC Encoding and Decoding on CUDA Platform - Liu Zhen; Wang Yunpei; Lu Lulu (2015 International Conference on Computational Science and Computational Intelligence (CSCI), 2015)
With the development of mobile Internet applications, the fourth generation mobile communication (4G) has been widely used, low-density parity-check (LDPC) codes have gradually become the first choice for 4G communication because of its superior performance. For the short of traditional encoding and belief propagation (BP) decoding algorithm, this paper adopts a method of parallel processing for LDPC encoding and decoding which is finally realized on the mobile terminal. On the CUDA platform, CPU scheduling and GPU parallelization are used to process a large number of repeated operations so that parallel encoding algorithm and heterogeneous parallel BP algorithm are achieved and the efficiency is significantly improved.